Obsesi Penerapan Syari’at Islam di Wilayah Lokal - Halim, Fatimah (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2015)
The existence of Islamic Sharia in Indonesian society since the beginning of the Islamic empire until now the rules are adhered to by the majority of Muslims in Indonesia. The obsession of society towards the implementation of Shari'a in the local area is to demand a special effort as a legal umbrella for the realization mempemudah application of Shari'a. In an effort to implement Shari'a adopted several strategies; that is; individual movements, social movements preaching and education, socio-political movements, movements and movements konstitusionalisasi legislation.